PERANCANGAN UI/UX APLIKASI PENCARI PEKERJAAN FREELANCE MENGGUNAKAN METODE DESIGN THINKING - Sadid, Moh Naufal; Prasetiyo, Budi (Politeknik Bisnis Indonesia, 2025)
The global shift in work patterns over the past decade has significantly increased the number of freelancers, including in Indonesia, where nearly one-third of the 145.79 million workforce engage in freelance work. This trend is driven by limited formal job opportunities, high qualification requirements, lack of work experience among job seekers, and restricted access to job vacancy information. Freelancing has become an adaptive alternative amid high unemployment rates among the productive-age population. This situation highlights the need for innovative digital platforms that connect freelancers with the job market through optimal user interface (UI) and user experience (UX) design. This study applies the design thinking method to develop the UI/UX of a freelance job search application called Jobble, addressing freelancers’ needs such as interest-based job searches, automatic CV generation, direct client communication, and skill-enhancing training. The resulting UI/UX design facilitates access to relevant job opportunities. A usability test using the System Usability Scale (SUS) achieved a score of 81.53, categorized as “Good,” indicating that Jobble’s UI/UX design meets user needs and has strong potential as a digital solution for freelancers in Indonesia.